Nanoscience The Science of the Small in Physics, Engineering, Chemistry, Biology and Medicine - Schaefer, Hans-Eckhardt.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
Nanoscience stands out for its interdisciplinarity. Barriers between disciplines disappear and the fields tend to converge at the very smallest scale, where basic principles and tools are universal. Novel properties are inherent to nanosized systems due to quantum effects and a reduction in dimensionality: nanoscience is likely to continue to revolutionize many areas of human activity, such as materials science, nanoelectronics, information processing, biotechnology and medicine. This textbook spans all fields of nanoscience, covering its basics and broad applications. After an introduction to the physical and chemical principles of nanoscience, coverage moves on to the adjacent fields of microscopy, nanoanalysis, synthesis, nanocrystals, nanowires, nanolayers, carbon nanostructures, bulk nanomaterials, nanomechanics, nanophotonics, nanofluidics, nanomagnetism, nanotechnology for computers, nanochemistry, nanobiology, and nanomedicine. Consequently, this broad yet unified coverage addresses research in academia and industry across the natural scientists. Didactically structured and replete with hundreds of illustrations, the textbook is aimed primarily at graduate and advanced-undergraduate students of natural sciences and medicine, and their lecturers.
IntroductionIntroduction and Some Physical Principlesphysical principles -- MicroscopyMicroscopy – Nanoscopynanoscopy -- Synthesis 3. Synthesis -- NanocrystalsNanocrystals – Nanowiresnanowires – Nanolayersnanolayers -- Carbon NanostructuresCarbon nanostructures – Tubes, Graphenegraphene , Fullerenesfullerenes , Wave-Particle Dualitywave-particle duality -- Nanocrystalline MaterialsNanocrystalline materials -- NanomechanicsNanomechanics – Nanophotonicsnanophotonics – Nanofluidicsnanofluidics -- NanomagnetismNanomagnetism -- Nanotechnology for ComputersNanotechnology for computers , Memoriesmemories , and Hard Diskshard disks -- NanochemistryNanochemistry – From Supramolecular Chemistrysupramolecular chemistry to Chemistry on the Nanoscalechemistry on the nanoscale , Catalysiscatalysis , Renewable Energyrenewable energy , Batteriesbatteries , and Environmental Protectionenvironmental protection -- Biology on the NanoscaleBiology on the nanoscale -- NanomedicineNanomedicine .
Keywords: Nanoscale science; Nanoscience; Nanostructures; Nanotechnology; Materials science; Surfaces (Physics).; Interfaces (Physical sciences).; Thin films; Biophysics; Biological physics; Nanochemistry; Nanoscale Science and Technology; Nanotechnology and Microengineering; Characterization and Evaluation of Materials; Surface and Interface Science, Thin Films; Biological and Medical Physics, Biophysics; Nanochemistry